P14.42 Neratinib for treatment of leptomeningeal metastases from HER2-positive breast cancer in extended access program: preliminary results. (9th September 2021) - Pellerino, A; Palmiero, R; Bruno, F; Mo, F; Muscolino, E; Franchino, F; Rudà, R; Soffietti, R
Abstract: BACKGROUND: Leptomeningeal metastases (LM) occur in 5% of human epidermal growth factor receptor 2 (HER2) breast cancer (BC) with a poor overall survival (OS) of 3 months. Neratinib is an oral, irreversible tyrosine kinase pan-inhibitor that was approved by FDA for the treatment of HER2-enriched BC, who completed a prior adjuvant trastuzumab-based therapy. The aim of the study was to evaluate the activity of neratinib in LM from HER2-positive BC after the failure of multiple lines of treatment, including trastuzumab. PATIENTS AND METHODS: Inclusion criteria were as follows: age ≥ 18 years; histological diagnosis of primary HER2-positive BC; newly-diagnosed LM according to LANO criteria; KPS ≥60 at the time of diagnosis of LM; coexistence of BM that have or not received WBRT or radiosurgery; systemic disease with a life expectancy of at least 3 months; concomitant drugs, including capecitabine, trastuzumab, TDM-1, pertuzumab, and hormone therapy were allowed, with the exclusion of lapatinib or other investigational agents. Neratinib was administered 240 mg daily continuously. The primary endpoint was the OS after the diagnosis of LM. Secondary endpoints were progression-free survival (PFS) following the diagnosis of LM, neurological benefit, radiological response rate, and tolerability. RESULTS: From January 2018 to April 2021, 9 patients with LM have been enrolled. Median age at the time of diagnosis of LM was 44 years (95%CI 36–59) with a median KPS of 80 (95%CI 60–90). Median time since LM onset from the diagnosis of primary BC was 42 months (95%CI 11–166), and patients underwent a median number of adjuvant treatments before LM of 3 (95%CI 2–5). Three patients developed LM alone, and other 6 had LM associated with multiple brain metastases. Six-months and 1-year OS were 66.7% and 22.3%, respectively, with a median OS of 8 months (95%CI 3–13*). Median PFS was 3.5 months (95%CI 2–6) after the start of treatment. A neurological improvement was reported in 2/9 patients (22.2%), while in other 4/9 patients (44.5%) was achieved a neurological stabilization lasting for a median time of 5 months (95%CI 2–19). The best radiological response was a stable disease in 5/9 patients (55.6%), while no complete or partial response were achieved according to LANO and RANO criteria, respectively. A CSF clearance was observed in 1 patient only (11.1%) following two months of neratinib. Grade III-IV adverse events were not reported, and 2 patients only (22.2%) had mild diarrhea correlated with neratinib. CONCLUSION: This is the first study that shows that neratinib might be a safe and effective treatment in LM from heavily pretreated HER2-positive BC.